PERAN PENYULUH PERTANIAN LAPANGAN DALAM MENDAMPINGI KELOMPOK TANI PADI DI KECAMATAN LALAN KABUPATEN MUSI BANYUASIN - Hidayat, Yusuf; Batubara, Mustopa Marli; Kurniawan, Rahmat (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2017)
The Role of Agricultural Extension Workers In Assisting Farmers Rice at Lalan Distric Musi Banyuasin Regency. This study aims to find out how the role of Agricultural Extension Workers In Assisting Farmers Rice at Lalan Distric Musi Banyuasin Regency. Research has been conducted in the of BP3K Karang Agung Tengah Lalan Distric Musi Banyuasin Regency June-August, 2016. The method used in this study is a survey method, sampling method used in this study is simple random sampling, data collection methods used in this research were interviews and observations of agricultural extension field and farmers instance guided by questions (quisoner ) which has been prepared. The results showed that the role of Agricultural Extension Workers in the BP3K Karang Agung Tengah is a consultant, facilitator, and educator resources to assist rice farmers groups in the of Lalan District Musi Banyuasin Regency.